FUNCTIONAL CHARACTERISTICS OF INTERNAL ANTI-CORRUPTION COMPLIANCE IN THE PUBLIC SECTOR AND THEIR IMPACT ON THE CORRUPTION PERCEPTION - Yevhenii Vandin; Hanna Buha; Oleksandr Kostiukevych; Alla Stechyshyn; Vasyl Dovganych (Financial and credit activity problems of theory and practice, 2026)
The aim of the study was to assess the impact of public integrity indicators, which reflect individual aspects of internal anti-corruption compliance, on the corruption rate in European countries. This impact was assessed using the regression analysis method and ANOVA test to identify statistically significant relationships between the studied indicators and the corruption perception. The sample included 38 countries in the European region and countries associated with the European public governance space. The data source was the OECD Public Integrity Indicators (PII) database (2026) and the Corruption Perceptions Index (CPI) data of Transparency International (2026). Additionally, the impact of selected macroeconomic and financial indicators on the CPI was assessed using data from the World Bank World Development Indicators (2026). As a result, it was found that the Adequacy of Implementation Structures and Reporting indicator (β = -0.3135) had the most significant impact in the Operational Activities and Results group. For the Transparency and Public Communication group, Inclusiveness and Transparency of Inter-Institutional and Public Consultations (β = -0.2530) and Transparency of Lobbying Activities and Prevention of Undue Influence (β = 0.2923) had a statistically significant impact. In the Regulatory Support group, Disciplinary Framework for Civil Servants (β = 0.4735) has the strongest impact. The additional analysis showed that GDP per capita had a statistically significant positive effect on the CPI (β = 0.0004; p < 0.0000), while GDP growth, inflation, and government expenditure did not demonstrate statistically significant individual effects. The study proves that formal regulatory requirements without proper institutional implementation do not provide the expected effect. Therefore, the fight against corruption requires a transition from improving legislative provisions to strengthening real mechanisms of internal control and open dialogue with the public. The obtained results can be used to improve the effectiveness of government anti-corruption programmes, taking into account the identified factors that influence the reduction of corruption rates.